Community Engagement and Research Translation in Puerto Rico's Northern Karst Region: The PROTECT Superfund Research Program. (November 2016) - Vega, Carmen M. V.; Brown, Phil; Murphy, Colleen; Figueroa, Abigail; Cordero, Jóse; Alshawabkeh, Akram
We describe here the social science-environmental health collaboration in PROTECT, the Puerto Rico Testsite for Exploring Contamination Threats, which is one of eighteen Superfund Research Program centers funded by the National Institute of Environmental Health Sciences. This collaboration has multiple facets: (1) create a holistic, unified research program that addresses the complexity of environmental contamination, (2) offer research participants an engaged and respectful interaction with the research team, (3) provide cross-training, in which the team's social scientists learn environmental health and the environmental health scientists learn social science, and (4) provide training for graduate students and post-docs in multiple disciplines in this burgeoning form of collaboration.